Biologi, neraca hayati, dan pemangsaan Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) pada Paracoccus marginatus Williams & Granara de Willink (Hemiptera: Pseudococcidae) - Wahyuningsih, Eka; Rauf, Aunu; Santoso, Sugeng (Perhimpunan Entomologi Indonesia, 2019)
Papaya mealybug, Paracoccus marginatus Williams & Granara de Willink (Hemiptera: Pseudococcidae), is an invasive pest that was detected for the first time in Indonesia in 2008. One of the common natural enemies is the predatory beetle Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae). The research was conducted with the objectives to determine the biology, life table parameters, and predation of C. montrouzieri on P. marginatus. Observation of biological and life table parameters and predation was conducted by introducing the predators into Petri dishes containing mealybugs. Eggs of C. montrouzieri hatched in 4.35 days. Mean developmental periods for 1st, 2nd, 3rd, and 4th instar larvae were 4.23; 4.21; 5.84; 5.93 days, respectively. The mean pre-pupal and pupal periods were 1.95 and 7.55 days, respectively. The longevity of male adults was 51.34 days, while that of females was 83.39 days. The number of eggs laid by a single female averaged 198.49. The net reproductive rate (Ro) was 117.11 individu/female/generation, intrinsic rate of increase (rm) was 0.073 individu/female/day, mean generation time (T) was 64.776 days, doubling time (Dt) was 9.426 days, and finite rate of increase (Î») was 1.076 per day. The 4th instar larvae of C. montrouzieri was the most voracious with numbers of P. marginatus eggs, 1st, 2nd, 3rd instar nymphs or adults consumed were 188.0; 53.4; 44.0; 26.8; or 15.6; respectively. Manly's preference index suggested that larvae, as well as adults of C. montrouzieri, preferred eggs and 1st instar nymphs of P. marginatus over other mealybug stages. Our study indicates the high potential of C. montrouzieri in the biological control of P. marginatus.